PENERAPAN TERAPI KOMPLEMENTER PIJAT OKSITOSIN DENGAN MINYAK ESENSIAL LAVENDER UNTUK MENINGKATKAN PRODUKSI ASI PADA PASIEN POST OPERASI SECTIO CAESAREA DI RS DEWI SRI KARAWANG - Yanti Rosmiyanti; Sumitro Sumitro; Desty Lismayanti; Sarini Sarini; Okti Rahayu Asih; Cindy Desrianti; Debi Novita (Journal of Innovation Research and Knowledge, 2025)
Suboptimal breast milk production frequently occurs in post-cesarean mothers due to pain, stress, and delayed lactogenesis. This condition may hinder the success of exclusive breastfeeding. One non-pharmacological intervention that can be used to improve breast milk production is oxytocin massage combined with lavender essential oil. This study aimed to determine the application of complementary oxytocin massage therapy using lavender essential oil to increase breast milk production in post-cesarean mothers at Dewi Sri Karawang Hospital. This study employed a descriptive design with a case study approach involving two post-cesarean postpartum mothers experiencing inadequate breast milk production. The intervention was administered once daily for 10–15 minutes over three consecutive days. Breast milk production was assessed using an observation sheet based on breast condition, milk secretion, and infant responses after breastfeeding. The results showed that before the intervention, the breast milk production scores were 2 (poor) for Subject 1 and 4 (fair) for Subject 2. After the intervention, the scores increased to 7 and 8, respectively. The improvement was indicated by increased milk secretion, softer breasts after breastfeeding, and calmer, more satisfied infants. It can be concluded that oxytocin massage using lavender essential oil may help improve breast milk production and secretion in post-cesarean mothers.